Pain Management: The Efficacy of Virtual Reality Therapy for Chronic Pain Relief: A Systematic Review - Asma Saleh Yahya Asseri et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Background: A person's mental health, physical health, and overall quality of life can all take a hit while they're dealing with chronic pain. Because conventional medicine has its limitations, supplementary treatments are sometimes necessary. One definition of virtual reality (VR) is a collection of computer-generated scenarios that provide the illusion of being physically present in a space. Virtual reality has already found use in the study of pain and mental health issues, and new evidence suggests it may have a role in the treatment of chronic pain. The purpose of this systematic review is to evaluate the efficacy of VR-based therapy for chronic pain treatment. Method: In order to evaluate the efficacy of virtual reality (VR) therapy in alleviating chronic pain, a systematic review was implemented. The review encompassed 17 studies that were published between 2016 and 2024 and evaluated the effects of VR therapy on patient satisfaction, pain intensity, pain interference with daily activities, mood, tension, sleep, and physical function. In order to account for correlated responses across repeated measures, the review employed a mixed-model framework and intention-to-treat analysis. The studies were chosen for their relevance to the efficacy of VR therapy for chronic pain relief, which included randomized controlled trials, cohort studies, and case series. Data was extracted from the included studies regarding study design, participant characteristics, VR intervention, outcome measures, pain alleviation, functional improvement, and patient satisfaction. The efficacy of VR therapy for chronic pain management was assessed through the analysis of the results. Results: Results of this systemic review revealed the effectiveness of virtual reality in decreasing the intensity of the pain among the samples of selected studies. In addition, all the VR interventions proved their efficacy in relieving pain caused by different injuries and causes. Conclusion: Virtual Reality (VR) is a non-invasive method that has demonstrated its efficacy in alleviating pain resulting from many causes, whether it is used in conjunction with other pain management methods or on its own. Keywords: Virtual reality (VR), Pain relief, Pain management, quality of life. Received Date: July 07, 2024 Accepted Date: July 28, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/179 DOI: https://doi.org/10.5281/zenodo.13622900